Dissolution Kinetics and Mechanism of Powder Detergent in Water - Yao, Xiaoyan; Tan, Hongsing; Geng, Daitao; Dang, Leping; Wei, Hongyuan (Asian Journal of Chemistry, 2015)
The dissolution process of powder detergent in deionized water was investigated systemically. The effects of percentage of sodium linear alkyl benzene sulfonate, particle size, solid/liquid ratio and dissolution temperature on the dissolution rate of powder detergent were investigated. The dissolution kinetics data was correlated by using heterogeneous dissolution models, which indicates that the dissolution process of powder detergent is in agreement with diffusion control model well. Based on the kinetics study, the mechanism of the dissolution process and roles sodium linear alkyl benzene sulfonate and sodium carbonate play in the dissolution were discussed.